The Oxford handbook of music and virtuality - Whiteley, Sheila, 1941-2015; Rambarran, Shara (New York City : Oxford University Press, 2016)
This work, edited by Sheila Whiteley and Shara Rambarran, brings together a multidisciplinary group of scholars who address issues such as artistic agency, the relationship between reality and illusion or simulation, and the construction of musical personae, subjectivities, and identities in a virtual world.
The Pre-Digital Virtual. "Seventeenth Heaven": Virtual Listening and its Discontents / Christian Lloyd ; "Nothing is Real": The Beatles as Virtual Performers / Philip Auslander and Ian Inglis ; Tom, Jerry and the Virtual Virtuoso / Sheila Whiteley ; Bring that Beat Back: Sampling as Virtual Collaboration / Rowan Oliver ; An Analysis of Virtuality in the Creation and Reception of the Music of Frank Zappa / Paul Carr -- Vocaloids, Holograms and Virtual Pop Stars. Vocaloids and Japanese Virtual Vocal Performance: The Cultural Heritage and Technological Futures of Vocal Puppetry / Louise H. Jackson and Mike Dines ; Hatsune Miku and Japanese Virtual Idols / Rafal Zaborowski ; Hatsune Miku, 2.0Pac and Beyond: Rewinding and Fast-Forwarding the Virtual Pop Star / Thomas Conner ; "Feel Good" with Gorillaz and "Reject False Icons": The Fantasy Worlds of the Virtual Group and their Creators / Shara Rambarran -- Second Life. Avatar Rockstars: Constructing Musical Personae in Virtual Worlds / Trevor S. Harvey ; Performing Live in Second Life / Justin Gagen and Nicholas Cook ; Live Opera Performance in Second Life: Challenging Producers, Performers and the Audience / t Human After All: Understanding Negotiations of Artistic Identity through the Music of Daft Punk / Cora S. Palfy ; Virtual Bands: Recording Music Under the Big Top / David Tough -- Communities and the World-Wide-Web. "Uploading" to Carnegie Hall: The First YouTube Symphony Orchestra / Shzr Ee Tan ; The Listener as Remixer: Mix Stems in Online Fan Community and Competition Contexts / Samantha Bennett ; Sample Sharing: Virtual Laptop Ensemble Communities / Benjamin O'Brien ; Stone Tapes: Ghost Box, Nostalgia, and Post-War England / David Pattie ; From Hypnagogia to Distroid: Postironic Musical Renderings of Personal Memory / Adam Trainer ; Bands in Virtual Spaces, Social Networking and Masculinity / Danijela Bogdanovic -- Sonic Environments and Musical Experience. From Environmental Sound to Virtual Environment Enhancing: Consuming Ambiance as Listening Practice / Thomas Brett ; App Music / Jeremy Wade Morris ; Alternative Virtuality: Independent Micro Labels Facing the Ideological Challenge of Virtual Music Culture: The Case of Finnish Ektro Records / t
Series statement from dust jacket.
Includes bibliographical references and index.
Keywords: Music and the Internet; Music -- Computer network resources